KARAKTERISTIK PENDERITA TUBERKULOSIS PARU BTA POSITIF DAN HASIL PENGOBATANNYA DI POLI PARU RSUD DELI SERDANG TAHUN 2011-2012 - tri hartini; Sori Muda Sarumpaet; Rasmaliah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
Pulmonary Tuberculosis (TB) is an infectious disease lung tissues caused by Mycobacterium tuberculosis. Prevalence of TB in 2010, there were 660.000 number of cases pulmonary TB in Indonesia, in North Sumatera there were 15.614 people, in Medan there were 2.152 people suffering from TB. In 2008, there were 1.276 people suffering from TB at Deli Serdang Regency. This research used a case-series design and large sample equal to great population that is 205 patient data. The results showed the proportion of people with pulmonary tuberculosis smear positive at pulmonary Poly Regency Hospital in Deli Serdang in 2011-2012, highest is age group 15-54 years (74,6%), male (69,3%), stayed at Deli Serdang regency (91,7%), new case (98,5%), category I (98,5%), supervised by family (81,5%), have sputum conversion at intensive phase (89,8%), have sputum conversion at advanced phase (79%), treatment outcome is cured (79%). The result of statistical analysis on the treatment outcome, there was a significant difference with residence (p=0,011), sputum conversion at intensive phase (p=0,000), and sputum conversion at advanced phase (p=0,000). However, there was no a significant difference with type of patient (p=0,112), category of medicial treatment (p=0,112), and supervised (p=0,370), For families and patient of pulmonary tuberculosis are required to follow the advice of health officials to conduct a re-examination of sputum in order to know how the subsequent treatment process.   Keyword : pulmonary tuberculosis smear positive, characteristic of patient